Measuring System Visual Latency through Cognitive Latency on Video See-Through AR devices - Gruen, Robert; Ofek, Eyal; Steed, Anthony; Gal, Ran; Sinclair, Mike; Gonzalez Franco, Mar (IEEE VR, 2020)
Measuring Visual Latency in VR and AR devices has become increasingly complicated as many of the components will influence others in multiple loops and ultimately affect the human cognitive and sensory perception. In this paper we present a new method based on the idea that the performance of humans on a rapid motor task will remain constant, and that any added delay will correspond to the system latency. We ask users to perform a task inside video see-through devices to compare latency. We also calculate the latency of the systems using hardware instrumentation measurements for bench-marking. Results show that measurement through human cognitive performance can be reliable and comparable to hardware measurement. Github Microsecond Arduino Latency Clock https://github.com/microsoft/Microsecond-Arduino-Latency-Clock